2012
DOI: 10.5551/jat.12013
|View full text |Cite
|
Sign up to set email alerts
|

Double-Dose Pravastatin Versus Add-On Ezetimibe with Low-Dose Pravastatin -Effects on LDL Cholesterol, Cholesterol Absorption, and Cholesterol Synthesis in Japanese Patients with Hypercholesterolemia (PEAS study)

Abstract: Adding ezetimibe to low-dose pravastatin achieves greater decreases in LDL-C, apo B, and cholesterol absorption markers than doubling the dose of pravastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…These data confirm literature data [35, 36]. Applying our new model, this suggests that the sum of DNCS and net PLCE compensates for the reduction in chol absorption rate.…”
Section: Scientific Evidence For the Proposed Modelsupporting
confidence: 89%
“…These data confirm literature data [35, 36]. Applying our new model, this suggests that the sum of DNCS and net PLCE compensates for the reduction in chol absorption rate.…”
Section: Scientific Evidence For the Proposed Modelsupporting
confidence: 89%
“…Fourteen studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27] involving 3105 participants were included for final quantitative analysis, among which 1558 (50.18%) participants received ezetimibe and statin combination therapy and 1547 (49.82%) received double-dose statin monotherapy. The average age of participants was 68.2 years with 30.9%-78.9% males.…”
Section: Search Resultsmentioning
confidence: 99%
“…Adding ezetimibe resulted in the highest LDL-C reduction rate among these three treatments. Some studies previously reported that adding ezetimibe to the original treatment was more effective in decreasing LDL-C levels than increasing statin doses [15,16].…”
Section: Discussionmentioning
confidence: 99%